2009
DOI: 10.22146/gamaijb.5538
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal Examination of Environmental Reporting Practices in Malaysia

Abstract: A content analysis of the annual reports of 96 Malaysian companies in 1999, 2003 and 2006 finds that the number of companies reporting on the environment increased from 47 percent in 1999 to 60 percent in 2003, and further increased to 67 percent in 2006. However, the extent of environmental reporting as measured by the number of environmental sentences and disclosure scores (using a self-constructed disclosure index) indicates a low quality of disclosure. Overall, the disclosure is ad-hoc and predisposed towa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 60 publications
3
28
0
Order By: Relevance
“…The index measures the comprehensiveness of the carbon information in terms of its breadth, depth and the reliability of the information. Therefore, the formation of reporting index is consistent with the concept of accountability and the principle of full disclosure of accounting information (Alrazi, Nik Ahmad & Sulaiman, 2009). The assessment of the quality of carbon reporting using disclosure index is essential in monitoring the carbon disclosure practices of companies over time and will increase competition between companies, hence ensuring a more comprehensive information (Hadley's study as cited in Jones & Alabaster, 1999).…”
Section: Sample Selection Data Sources Instrumentation and Analysismentioning
confidence: 63%
“…The index measures the comprehensiveness of the carbon information in terms of its breadth, depth and the reliability of the information. Therefore, the formation of reporting index is consistent with the concept of accountability and the principle of full disclosure of accounting information (Alrazi, Nik Ahmad & Sulaiman, 2009). The assessment of the quality of carbon reporting using disclosure index is essential in monitoring the carbon disclosure practices of companies over time and will increase competition between companies, hence ensuring a more comprehensive information (Hadley's study as cited in Jones & Alabaster, 1999).…”
Section: Sample Selection Data Sources Instrumentation and Analysismentioning
confidence: 63%
“…While there are fewer social and/or environmental disclosure studies in developing countries, the results appear to be similar in that studies found that extent of environmental disclosures is very minimal and disclosures tend to be self‐laudatory and very general information which is not easily verifiable (Basalamah & Jermias, ; De Villiers & Van Staden, ; Sumiani et al ., ; Islam and Deegan, ; Alrazi et al ., ). Alrazi et al .…”
Section: Review Of the Literaturementioning
confidence: 97%
“…The literature review suggests that while environmental disclosures were generally increasing, the extent and quality are still low, both in developed and developing countries (Niskala & Pretes, ; Moneva & Llena, ;Alrazi et al ., ). Most disclosures are self‐laudatory and confined to general, descriptive statements (Deegan & Gordon, ; Deegan & Rankin, ; Laine, ).…”
Section: Review Of the Literaturementioning
confidence: 97%
See 2 more Smart Citations